2006
DOI: 10.1158/0008-5472.can-06-1679
|View full text |Cite
|
Sign up to set email alerts
|

EBV Latent Membrane Protein 1 Up-regulates Hypoxia-Inducible Factor 1α through Siah1-Mediated Down-regulation of Prolyl Hydroxylases 1 and 3 in Nasopharyngeal Epithelial Cells

Abstract: Hypoxia-inducible factor 1 (HIF1) is up-regulated in most malignant tumors usually via interruption of ubiquitination and proteasomal degradation of its subunit A. Recently, we have shown that the principal EBV oncoprotein, latent membrane protein 1 (LMP1), activates HIF1A and subsequently expression of HIF1-responsive genes in epithelial cells. Here, we explore the mechanism for HIF1A activation by LMP1 in nasopharyngeal epithelial cells: LMP1 up-regulates the level of Siah1 E3 ubiquitin ligase by enhancing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 47 publications
(78 reference statements)
1
105
0
Order By: Relevance
“…Recently, we demonstrated that Epstein-Barr virus (EBV)-associated latent membrane protein 1 (LMP1) increased the expression of HIF1α via the induction of Siah1 in human nasopharyngeal epithelial cells [16]. Moreover, EBV is closely related to the carcinogenesis of NPC [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that Epstein-Barr virus (EBV)-associated latent membrane protein 1 (LMP1) increased the expression of HIF1α via the induction of Siah1 in human nasopharyngeal epithelial cells [16]. Moreover, EBV is closely related to the carcinogenesis of NPC [1].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies showed that LMP1 transfection of lymphoblastoid and carcinoma cell lines induced HIF-1a in vitro [14,15]. If the same pathway were active in vivo, it might compel clinical trials of newly available antiangiogenic agents to thwart the effects of LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to in vitro models in which LMP1 induced HIF-1a [14,15], in vivo settings can be expected to behave in a much more complicated fashion. Levels of host genes are influenced, at least in part, by the local tumor environment including oxygenation status, which is a potent regulator of HIF stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent co-immunoprecipation studies indicate EBV LMP1 enhances the stability of Siah1 E3 ubiquitin ligase, inducing proteasomal degradation of PHD-1 and PHD-3 that normally tag HIF-1α for degradation. LMP1 thus prevents formation of the VHL/HIF-1α complex, providing a mechanism for HIF-1α stabilization during EBV nasopharyngeal cell infection [44].…”
Section: Hif-1α Dynamics In Viral Infectionmentioning
confidence: 99%